Pengaruh Kualitas Pelayanan, Persepsi Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Di Restoran Soto Bebek Bu Sri - Farah Shaussan; Aris Budiono (LPPM Universitas Asa Indonesia, 2025)
This research was conducted with the aim of analysing the influence of service quality, price perception, and product quality on consumer purchasing decisions at Soto Bebek Bu Sri Restaurant. The methodology used in this study is a quantitative approach through surveys. The sampling technique employed was accidental sampling with 100 participants. Data analysis was carried out using multiple linear regression analysis supported by SPSS version 29 software. The results of this study indicate that product quality has a significant impact on purchasing decisions. Meanwhile, service quality and price perception do not have a significant effect on purchasing decisions.